Communitarian Constitution. - Breslin, Beau (The Johns Hopkins University Press, 2006)
Bowling Alone, the title of Robert Putnam's 1995 article (later a bestselling book) perfectly captured a sense of national unease: Somewhere along the way, America had become a nation divided by apathy, and the bonds that held together civil society were disappearing. But while the phrase resonated with our growing sense of atomization, it didn't describe a new phenomenon. The fear that isolation has eroded our social bonds had simmered for at least two decades, when communitarianism first emerged as a cogent political philosophy. Communitarianism, as explained in the works of Michael Sandel, Alasdair MacIntyre, Amitai Etzioni, and others, elevates the idea of communal good over the rights of individuals. Throughout the 1980s and 1990s, communitarianism gained popular and political ground. The Clintons touted its principles in the '90s, and the two presidents Bush make frequent references to its central tenets. In its short life, the philosophy has generated plenty of books, both pro and con. Beau Breslin's authoritative and original examination, The Communitarian Constitution, contributes to the debate from a wholly original standpoint. Existing critiques focus on the debate between liberalism and communitarianism - in other words, the conflict between individual rights and the communal good. Breslin takes an entirely different stance, examining the pragmatic question of whether or not communitarian policies are truly practicable in a constitutional society. In tackling this question, Breslin traces the evolution of American communitarianism. He examines Lincoln's unconstitutional Civil War suspension of habeas corpus and draws on Federalist and Anti-Federalist arguments, pegging the Anti-Federalists as communitarians' intellectual forebearers. He also grounds his arguments in the real world, examining the constitutions of Germany and Israel, which offer further insight into the relationship between constitutionalism and communitarianism. At a moment when American politicians and citizenry are struggling to balance competing needs, such as civil rights and homeland security, The Communitarian Constitution is vital reading for anyone interested in the evolving tensions between individual rights and the good of the community.